Teachers’ Work Motivation in Extended Opportunity Schools under the Trat Primary Educational Service Area Office - Chanpoom, Teeraphan; การีเวท, สมนึก; ประวัติรุ่งเรือง, ประเสริฐ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to 1. investigate the level of teachers’ work motivation, 2. compare teachers’ work motivation according to gender, age, educational attainment, work experience, and school size, and 3. explore guidelines for enhancing teachers’ work motivation in extended opportunity schools under the Trat Primary Educational Service Area Office. The sample consisted of 214 teachers, selected through stratified random sampling based on school size. The research instruments were a five-point rating-scale questionnaire and open-ended questions. Data were analyzed using frequency, percentage, mean, standard deviation, independent samples t-test, and one-way analysis of variance (ANOVA), while open-ended responses were analyzed through content analysis.           The findings revealed that: 1. teachers’ work motivation was overall at a high level, with career advancement showing the highest mean score and achievement showing the lowest mean score; 2. overall, work motivation did not significantly differ by personal factors; however, when considered by dimension, significant differences were found by gender in recognition, responsibility, and career advancement, and by age in job characteristics, whereas no significant differences were found by educational attainment, work experience, or school size; and 3. guidelines for enhancing teachers’ work motivation, derived from open-ended responses of teacher participants who directly worked in extended opportunity schools, included reducing non-instructional workload, providing adequate resources and instructional media, improving school management and internal communication, and fostering a supportive work atmosphere conducive to teacher motivation.